Ética nas relações sociais: o "jeitinho brasileiro" - Fiel, Maristela Silva (2010)
This study has lhe objective of understanding how lhe Brazilian social context's transgression interferes in lhe "expansion of himseJr'; which judgments people do in situations where people transgress rufes with lhe intention of adapt them to their own desires ("Brazilian knack'?; how they guide their actions in that context and which principies they define in their relationships among pairs, with lhe institutions and with lhe social net. To construct this study we accomplished a qualitative and an interpretative research, giving emphasis on lhe building of a reality based on lhe social nature and lhe importance of understanding lhe phenomenon in lhe contextual and systemic way. Focal groups where used as research instruments, which allowed us to dialogue about this topic with lhe participants and co-build knowledge on lhe studied phenomenon. Ten people of both sexes were interviewed, ages varying between 18 and 52 years old, socioeconomic levels C and B (data from lhe '~gência Brasil') and very low or even nulllevels of vulnerability (data from lhe 'índice Paulista de; Vulnerabilidade . Social - IPVS'). In lhe analysis and interpretation of lhe content Df lhe interviews we built four tables with lhe following thematic axis; ethics, moral, transgression and values; they were then divided in subclasses. The results showed that lhe individualism, lhe fact of "taking advantage", lhe competition and lhe decline of merit are guidelines in lhe search of a positive self concept. We live in a culture . 1 where what is shown is hierarchically above lhe good, lhe right and of what is fair